The Mediating Effect of Psychological Ownership on the Relationship Between Servant Leadership and Organizational Citizenship Behaviors in Kano, Nigeria - Bambale, Abdu Ja'afaru (2013)
This study examines the determinants of employee organizational citizenship behaviors (OCBs) among low and middle level employees of utility sector organizations in Nigeria. Primarily, this study explored the role of psychological ownership (PO) as a mediator on the relationship between servant leader behaviors (SLBs) including emotional healing, creating value for the community, conceptual skills and helping subordinates grow and succeed, and employee OCBs. Partial Least Squares Method (PLS) algorithm and bootstrap techniques were used to test the study hypotheses. The results provided support for most of the hypothesized relationship for the study. Specifically, emotional healing, conceptual skills, helping subordinates grow and succeed, putting subordinates first, and psychological ownership are significantly and positively related to both organizational citizenship behaviors that benefit the individual (OCB-I), and the organization (OCB-O). However, creating value for the community is significantly and negatively related to both forms of organizational citizenship behaviors. Additionally, emotional healing, helping subordinates grow and succeed, and putting subordinates first were significantly and positively related to psychological ownership, while creating value for the community was significantly and negatively related to psychological ownership. Furthermore, the results of mediation indicated that six of the ten hypotheses are significant. Therefore, significant positive effects of emotional healing, conceptual skills, helping subordinates grow and succeed, and putting subordinates first and psychological ownership suggest that the variables are important in motivating OCBs. As such, employees should be encouraged to exhibit these behaviors for enhanced performance of organizational citizenship behaviors. Enhanced performance of organizational citizenship behaviors can improve the overall effective function of organizations. Contributions, limitations, and implications are discussed.